The effect of bilingualism on the processing of clustering and switching in verbal fluency tasks - Najme Mardani; Mohammad Pourjafari; Mohammad Amin Irandegani; Nassim Ahmadi; Kowsar Baghban (Shiraz University of Medical Sciences, 2020)
Background: This study examined the effect of bilingualism on the processing of clustering and switching in verbal fluency tasks in Farsi-Balochi bilinguals. Methods: Ninety participants entered this study, including 45 Farsi monolinguals and 45 Farsi-Balochi bilinguals. All participants were male university students between the ages of 18 to 24 years. Verbal fluency tests were performed and the clustering and switching scores were calculated. Data was analyzed in SPSS-16 software. Results: The monolingual group obtained a score of 32.84 in the total semantic fluency task and 24.13 in the phonemic fluency task, while the bilingual group obtained 30.70 in the semantic task and 29.37 in the phonemic task. The number of switches between the clusters and the mean cluster size were 35.82 and 2.6 in the monolingual group and 38.65 and 2.26 in the bilingual group, respectively. The difference between groups in phonemic fluency, phonemic switching, and semantic clustering was significant (p˂0.05). Discussion: The bilingual group performed better in phonemic fluency and switched more between the clusters. Meanwhile, the monolinguals produced more words in each cluster than the bilinguals.